Physio-chemical investigation and analyses of contaminants in groundwater flow. Case study - Papalanto, Ifo local government area, South - Western Nigeria, Ogun State - Olorode, Oluwaseun Deborah; Adeneye, Samuel Olaolu; Morakinyo, Aderonke Deborah; Oyeneyin, Opeyemi Aliu; Akpochafor, Michael Onoriode; Omojola, Akintayo Daniel (The European Research Journal, 2019)
Objectives: Groundwater is the primary source of drinking water for roughly, a third of the world’s population, but highly vulnerable to pollution. A thorough research was carried out to investigate the extent of groundwater contamination on four active dumpsite and a control point at Papalanto, Abeokuta area, and South-Western Nigeria. Methods: Domestic wells in the area facilitated the resources for water chemistry. A total of five groundwater samples were collected from wells located close to different dumpsite in the study area, to determine the extent of groundwater contamination. Physio-chemical analysis was carried out on the five water samples; the basic method adopted in the chemical analysis includes titrimetric method, atomic absorption spectroscopy and calometric method. Results: The results showed that water quality parameter like temperature, pH, taste, odour, total solids, sulphate, copper, iron, zinc, cadmium and chromium are in appropriate standard prescribed by WHO and NSDWQ. Other physical parameters like color, turbidity, conductivity, total suspended solids, total dissolved solid, total hardness, total alkalinity, total acidity, calcium, magnesium, chloride, nitrite, manganese, lead, nickel, nitrate, have higher values than the authorized standard value, which directly or indirectly affect the water content found in the area for drinking purpose. These features could be attributed to the possible activities of contaminants facilitated by leachate plume from the dumpsite. Conclusions: The study shows that the regolith aquifer in the area of study is highly vulnerable to pollution from the refuse dumps. From the geophysical and physio-chemical analysis carried out, the values of most parameters obtained in the water samples collected at locations close to the leachate have been confirmed to be higher than those collected at locations away from the leachate. Hence, the groundwater near the leachate is confirmed contaminated.